2015
DOI: 10.1038/srep11185
|View full text |Cite
|
Sign up to set email alerts
|

Software-aided automatic laser optoporation and transfection of cells

Abstract: Optoporation, the permeabilization of a cell membrane by laser pulses, has emerged as a powerful non-invasive and highly efficient technique to induce transfection of cells. However, the usual tedious manual targeting of individual cells significantly limits the addressable cell number. To overcome this limitation, we present an experimental setup with custom-made software control, for computer-automated cell optoporation. The software evaluates the image contrast of cell contours, automatically designates cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The non-linear nature of the excitation process provides intrinsic 3D-imaging capability by minimizing out-of-focus excitation. A similar reasoning applies to harmonic generation microscopy (Sun, 2005) and other nonlinear interactions between light and cells/ tissue like laser-assisted cell transfection (Breunig et al, 2015). Under ideal conditions, when the incident pulses are only minimally absorbed and/or scattered, high resolution imaging at depths in the mm range inside tissue can be achieved in vivo (Kobat et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…The non-linear nature of the excitation process provides intrinsic 3D-imaging capability by minimizing out-of-focus excitation. A similar reasoning applies to harmonic generation microscopy (Sun, 2005) and other nonlinear interactions between light and cells/ tissue like laser-assisted cell transfection (Breunig et al, 2015). Under ideal conditions, when the incident pulses are only minimally absorbed and/or scattered, high resolution imaging at depths in the mm range inside tissue can be achieved in vivo (Kobat et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…For instance, the delivery of gene-editing tools could be used to manipulate cells and tissues for regenerative medicine or engineer cells for personalized cell therapies [4][5][6][7]. Intracellular delivery methods include biological vectors such as viruses, chemical modifications of delivery cargoes such as lipofection, and physical techniques such as microinjection, electroporation, and optoporation [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. While research efforts have led to a continuous increase in efficiency and sophistication, each of the currently available approaches has its own advantages and disadvantages.…”
Section: Currently Available Intracellular Delivery Techniquesmentioning
confidence: 99%
“…Optoporation, a physical delivery technique, utilizes a tightly focused laser beam to create a transient pore in the cell membrane [18,19,33,34]. This technique offers high delivery efficiency, high cell viability and is versatile with respect to cargo and cell type.…”
Section: Laser-mediated Cell Poration For Intracellular Deliverymentioning
confidence: 99%
“…With image processing, the location of the individual cells can be determined. In combination with an auto-focus system to control the axial position of the photoporation laser beam, this allows cells to be photoporated in an automated fashion [107,108]. In one example, it was demonstrated that ~300 cells/min can be photoporated that way [107].…”
Section: Experimental Procedures For Direct Laser-induced Photoporationmentioning
confidence: 99%
“…In combination with an auto-focus system to control the axial position of the photoporation laser beam, this allows cells to be photoporated in an automated fashion [107,108]. In one example, it was demonstrated that ~300 cells/min can be photoporated that way [107]. Finally, a microfluidic approach has also developed in an attempt to increase photoporation throughput, with cells flowing one by one through the focused photoporation laser beam.…”
Section: Experimental Procedures For Direct Laser-induced Photoporationmentioning
confidence: 99%